On the distortion of UWB circularly polarized time-domain pulses in presence of rotation - Narbudowicz, Adam (My University, 2019)
The paper provides a first theoretical study on the effect of rotational Doppler on circularly polarized pulsed communication. Despite the circularly polarized communication being considered immune to signal fading due to rotary misalignment, such misalignment will cause a frequency-invariant phase-shift. This phase shift will significantly distort the shape of the time-domain pulse. The property can be used for integration of orientation sensing into well establish pulse-based localization. However, it has also the potential to distort communication for some pulse-modulated UWB systems.
Keywords: rotational Doppler; polarized pulsed communication; integration of orientation; Wireless sensing; Localization; Circular Polarization; Pulse modulation; Ultra-wideband (UWB)